Electronic Breast Imaging Learning Module: A Way to Enhance the Breast Imaging Rotation for Residents - Carolynn DeBenedectis; Rebecca Hultman; Gopal Vijayaraghavan (Association of American Medical Colleges, 2015)
Abstract This resource is an electronic breast imaging learning module designed to improve resident learning, decision-making ability, and overall experience on the rotation. It consists of three modules that review key concepts in breast imaging and contain interactive cases. The modules also include pre− and posttests for self-assessment. The electronic breast imaging learning modules are administered at the beginning of each breast imaging rotation each year of residency. On the first day of the resident's breast imaging rotation, the resident takes the self-assessment test that is appropriate for his/her year in training. The resident answers the questions on the answer sheet but does not correct the test yet. The resident then reviews the electronic learning module that is appropriate for his/her year in training. After the resident completes the module, he/she takes the self-assessment test appropriate for his/her level in training and answers the questions on the answer sheet. The resident then self-corrects the pre− and posttests to see how he/she did and if there is improvement from the pretest to the posttest. The first year we implemented the electronic breast imaging learning module, there was an increased score of 7% on the posttest compared to the pretest. All of the residents were surveyed after using the learning module: 89% of the residents gave it excellent for an overall rating, and 100% of the residents said the module was easy to use. Residents also commented that the learning module helped them understand better what was expected of them for their level of training on the rotation. Some residents also commented that it helped them approach breast imaging cases in a more organized manner.